The Effectiveness of Performance Management Systems in Driving Employee Productivity - Maxwell Smith Ogbotor; Mbagwu Ignatius Nwabudo (CV. Proaksara Global Transeduka, 2025)
This study explores the relationship between Performance Management Systems (PMS) and employee productivity, particularly in the context of diverse work environments, cultural differences, and varying legal landscapes. Effective PMS can enhance employee motivation, engagement, and productivity by providing clear goals, regular feedback, and opportunities for development. By implementing a well-designed PMS, organizations can stimulate managers to develop strategic plans, set ambitious targets, and closely monitor activities, ultimately promoting sustained value creation. The significance of performance management in enhancing employee productivity cannot be overstated. A people-centric approach to performance management focuses on developing and motivating employees to achieve desired goals, while an integrated and continuous approach enables organizations to measure and actively manage performance, and improve effectiveness. This inquiry employs Self-Determination Theory (SDT) as a conceptual lens to elucidate the intrinsic psychological requisites that animate workforce motivation and efficacy. SDT posits that individuals exhibit the highest degree of volition when they experience autonomy, proficiency, and connectedness within their occupational sphere. Through the infusion of SDT precepts, institutions may cultivate milieus that safeguard self-governance, nurture advancement and mastery, and engender collegial synergy, thereby sustaining motivation that is both enduring and self-propelled. The outcomes of this investigation are anticipated to enrich extant scholarship by delineating exemplary practices applicable across heterogeneous contexts, ultimately empowering organizations to unseal the latent reservoir of performance management and to attain heightened productivity, efficiency, and operational potency. Moreover, the findings will furnish discerning insights for enterprises endeavoring to refine their human capital and realize overarching strategic imperatives.